Pengenalan Struktur Tumbuhan dan Fungsi Tumbuhan Berbasis Video Animasi 2D - Bagas Setyawan; Sri Widiyanti; Tinuk Agustin (STIKes Ibnu Sina Ajibarang, 2024)
Learning videos are a medium or tool used in the educational process to convey information, concepts or learning materials to students using visual and audio elements. The aim of this design is to make teaching and learning activities enjoyable and effective. This learning video was made using Adobe After Effects to create the animation. The design of this learning video uses the ADDIE method. Then to collect data using a questionnaire with 6 question indicators, from the 6 question indicators a score of 57.5% was obtained, so it can be concluded that this learning animation video can be said to be successful and able to help in teaching and learning activities at MIM Pundungrejo. , Tawangsari, Sukoharjo. This 2D animated learning video contains roots, stems, leaves, fruit and flowers. This design aims to make students interested in studying and knowing the structure of plants and their functions in everyday life.